Evaluation of a Metal Supported Ni-YSZ / YSZ / La2NiO4 IT-SOFC Elaborated by Physical Surface Deposition Processes. (2nd June 2015) - Fondard, Jérémie; Bertrand, Pierre; Billard, Alain; Skrabs, S; Franco, Thomas; Fourcade, Sébastien; Batocchi, Pierre; Mauvy, Fabrice; Bertrand, Ghislaine; Briois, Pascal
Abstract : The elaboration of the last generation metal supported IT-SOFC complete cell by dry surface deposition processes is really challenging. Atmospheric Plasma Spraying (APS) and Reactive Magnetron Sputtering (RMS) processes are respectively adapted to deposit Ni-YSZ anode and YSZ electrolyte layers. RMS is also used to coat a thin and dense La2 NiO4 (LNO) cathode layer. In this work, we have elaborated a complete cell on metallic support (ITM) produced by PLANSEE SE. The innovative LNO cathode layer was compared with screen-printed LNO layers, with and without RMS bonding layer. Electrochemical and Voltametry tests were performed on these samples. It reveals lower performances than literature due to the high density of the RMS cathode layer, and too high temperature during sintering step which deteriorate layers manufactured by RMS and metallic substrate. Nevertheless, using LNO bonding layer manufactured by RMS seems to be an interesting way to improve the polarization resistance of the cell.